2019
DOI: 10.1161/strokeaha.118.023093
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Use of Standard- and Low-Dose Non–Vitamin K Oral Anticoagulants in Asian Patients With Atrial Fibrillation

Abstract: Background and Purpose— Limited data are available describing the relative effectiveness, safety, and optimal dosing of non–vitamin K antagonist oral anticoagulants (NOACs) for treatment of nonvalvular atrial fibrillation in East Asian patients. We tried to compare effectiveness and safety outcomes of standard- and low-dose NOACs and warfarin in this population. Methods— Using nationwide administrative claims-based datasets from the Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 32 publications
4
109
0
1
Order By: Relevance
“…In terms of retinal vascular occlusion, female patients showed a higher risk of retinal vascular occlusion with NOACs than male patients. Our study did not investigate the dosage by sex, while more female patients are known to be prescribed lower dose of NOACs in Korea 30 . This may result in a higher risk of retinal vascular occlusion with lower efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of retinal vascular occlusion, female patients showed a higher risk of retinal vascular occlusion with NOACs than male patients. Our study did not investigate the dosage by sex, while more female patients are known to be prescribed lower dose of NOACs in Korea 30 . This may result in a higher risk of retinal vascular occlusion with lower efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the exact doses for anticoagulants were not investigated in this study. There is a tendency in Asian countries to use the lower doses of NOACs in clinical practice 2,29,30 , which may have affected the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of four major clinical trials reported that compared to warfarin, DOACs showed a significantly lower risk of stroke or systemic embolism in patients with AF and a history of stroke [22]. Several studies using population-based claims databases have investigated the effectiveness and safety of different types of DOACs compared with that of warfarin in patients with AF and a history of stroke [9,[23][24][25]. A Danish nationwide cohort study reported that the risks of ischemic stroke or systemic embolism associated with apixaban, dabigatran, and rivaroxaban were comparable to those associated with warfarin [23].…”
Section: Discussionmentioning
confidence: 99%
“…The use of reduced dose apixaban in non-eligible patients (those aged under 75 years and without chronic kidney disease) attenuated the benefit observed in the comparison between a standard dose apixaban and warfarin. 29) In patients with AF and those who were underweight (≤60 kg), on-label dosing of NOACs showed the best net clinical benefit. 26) In patients who were eligible (CrCl ≥50 mL/min), both on-label rivaroxaban 20 mg once daily and off-label underdosed rivaroxaban 15 mg once daily, showed better effectiveness and safety than warfarin.…”
Section: Clinical Impact Of Off-label Dosing Of Noacsmentioning
confidence: 99%
“…20) In the Asian population, reduced doses of NOACs were mainly prescribed to patients with AF, and the use of such doses was considerably more common in the Asian population than in the non-Asian population ( Table 2). [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] There are several potential reasons for the more frequent use of reduced dose NOACs in Asian patients with AF. First, Asians generally have a lower body weight and smaller body size than non-Asians, who were represented to a greater degree in the pivotal RCTs.…”
Section: Real-world Practice In Asian Populationmentioning
confidence: 99%